Associations between an inflammatory diet index and nonunion: a prospective study of 172,839 UK biobank participants - Su, Jiemao; Fan, Wenxuan; Kong, Keyu; Wang, Yifan; Zhai, Zanjing; Zhang, Jingwei; Jin, Minghao; Qi, Yansong; Xu, Yongsheng (Frontiers in Nutrition, 2025)
PurposesThis study utilizes prospective cohort data from the UK Biobank to investigate the association between the energy-adjusted dietary inflammation index (E-DII) and the development of fracture nonunion.MethodsIn this study, COX regression was used to analyze the correlation between E-DII and nonunion. Among 172,839 participants free of prior nonunion at baseline, 2,341 (1.4%) developed nonunion during a median follow-up of 14.2 years. E-DII scores, calculated from five separate 24-h dietary recall assessments, were used to quantify dietary inflammatory potential, with higher values indicating pro-inflammatory patterns.ResultsMultivariable-adjusted analyses revealed that participants with anti-inflammatory dietary patterns (E-DII < −1) exhibited a significantly elevated risk of impaired fracture healing compared to those with pro-inflammatory diets (E-DII > 1), yielding an adjusted hazard ratio (HR) of 1.89 (95% CI: 1.45–3.11). A nonlinear U-shaped dose–response relationship was identified, with the nadir of nonunion risk observed at E-DII values between 0.3 and 1.2. Conversely, values outside this range were associated with progressively higher risks. Transcriptomic profiling identified differential expression of 35 inflammation-related genes—including CD3E and CX3CR1—significantly downregulated in nonunion cases compared to controls. These genes are functionally enriched in pathways governing immune response regulation and leukocyte activation.ConclusionThese findings propose that a moderately pro-inflammatory dietary pattern may confer protection against impaired bone healing, whereas both strongly anti-inflammatory and excessively pro-inflammatory diets were associated with compromised healing outcomes. Based on these results, tailored dietary strategies designed to optimize inflammatory homeostasis during fracture recovery are recommended to enhance clinical outcomes.